Algorithmic design of a product based on customer data - Francisco, Álvaro Miguel Cruz (2022)
There is a growing trend of using computers creatively in order to enrich the design process. There are three Computational Design techniques that stand-out: Parametric Design, Generative Design and Algorithmic Design. This dissertation intends to test the viability of using these techniques in a context of product development. These techniques show tremendous potential for products that can be customizable by consumers, exploring the combination of various manufacturing methods. To achieve these goals a case study with customization potential and the ability to test algorithmic design techniques has been selected. The results originate from 2 approaches: a generative approach and an algorithmic approach, with each having different evaluation methods. The generative approach is able to explore a solution search space and compares the generated curvatures, whilst the algorithmic approach takes advantage of rapid prototyping principles. The performance indicators for the case study’s conception stage using CD techniques are very positive, but the production stage needs more research.